HUKUM INDONESIA DALAM PERSPEKTIF KESEJARAHAN DAN MODERNISASI HUKUM NASIONAL - Budiyanto S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
A thought that law exists only if there is its act as logistics said has isolated law from its social reality cannot be defended anymore. In the modernization of law, there is a need for digging values of law which live inside the society or customary law which contains universal values. The law must be integrated well with its social reality, not only it pursues the certainty of law, but also it must be in accordance to justice and its usefulness for the society. Therefore, the law cannot disregard the laws which live inside the society besides it still accept inputs/positive influences fromthe outside. The modernization of law must be based on law which can be accepted by the society, both from customary law and other types of law which influences. The potential of customary law has often been nullified because it is regarded as local and traditional. Whereas in customary law there is also written law such as Law in Majapahit era andAmanna Gappa in Sulawesi.